Ticket to ride. [games] London - Moon, Alan R., 1952-; Moon, Alan R., 1952- (Days of Wonder, 2019)
"In this fast-paced Ticket to Ride game, players race one another to claim the most important bus lines and complete their destination tickets, connecting districts in the capital of the United Kingdom. The elegantly simple gameplay of this stand-alone version of Ticket to Ride is ideal for both beginners and seasoned players"--Container.